Synthesis of Peripherally Arylated Tetrathiafulvalenes Extended with an Anthraquinoid Spacer via Pd-Catalyzed C–H Arylation and Construction of a Double-Helical Cobalt-Based Metal-Organic Framework - Yoshimura, Aya; Henmi, Keisuke; Kimura, Hitoshi; Sakakibara, Ryo; Ochi, Rika; Shirahata, Takashi; Yorimitsu, Hideki; Misaki, Yohji (Synthesis, 2021)
Peripherally arylated tetrathiafulvalenes with an anthraquinoid spacer (TTFAQs) have been synthesized by using palladium-catalyzed direct C–H arylation of the 1,3-dithiole rings. Electrochemical analysis by cyclic voltammetry has revealed that the new tetraarylated TTFAQs show one pair of simultaneous two-electron transfer waves as the parent TTFAQ does. The hydrolysis of the tetra(p-ethoxycarbonylphenyl)-substituted derivative affords the corresponding tetracarboxylic acid, which forms a new double-helical metal-organic framework upon complexation with cobalt(III) nitrate.
Keywords: tetrathiafulvalene; anthraquinoid; palladium catalysis; C–H arylation; electrochemical properties; metal-organic frameworks; X-ray diffraction